China and India in Central Asia a new "great game"? - Jean - Francois Huchet; Sebastiaen Peyrouse; Bayram Balc (Sciences PO series in international relations and political economy, 2010)
This book looks at how China and India's growing interests in Central Asia disrupt the traditional Russia-U.S. 'Great Game' at the heart of the old continent. In the years to come, both Asian powers are looking to redeploy their rivalry on the Central Asian and Afghan theatres on a geopolitical, but also political and economic level